Whole‐body magnetic resonance imaging for staging Langerhans cell histiocytosis in children and young adults. Issue 2 (1st November 2022) - Perrone, Anna; Lakatos, Karoly; Pegoraro, Francesco; Trambusti, Irene; Fotzi, Ilaria; Selvi, Valeria; Prosch, Helmut; Sertorio, Fiammetta; Pötschger, Ulrike; Favre, Claudio; Conte, Massimo; Minkov, Milen; et al.
Abstract: Introduction: Radiographic skeletal survey (R‐SS) is the standard imaging technique for the initial staging of Langerhans cell histiocytosis (LCH). Whole‐body magnetic resonance imaging (WB‐MRI) has been proposed as an effective, radiation‐free alternative. Methods: We prospectively assessed patients with LCH followed at three tertiary centers in Italy and Austria. Two national study protocols were independently designed, and data were then pooled to increase the power of their findings. R‐SS and WB‐MRI were performed at diagnosis and repeated at the follow‐up to confirm the nature of the identified lesions and to study their evolution. Results: Data from 67 patients were analyzed (52 from Italy and 15 from Austria). Compared to R‐SS, WB‐MRI identified 29 additional skeletal lesions in 14 patients (including two false‐positive lesions). Two skeletal lesions were detected at R‐SS and missed at WB‐MRI (false negative). Per‐lesion sensitivity rates were 78.6% (95% CI: 71.0–85.9) for R‐SS and 98.4% (95% CI: 94.4–99.8) for WB‐MRI, respectively. Based on WB‐MRI findings, six patients would have been upstaged to a higher risk class than staging with R‐SS. Conclusions: WB‐MRI had a significantly higher detection rate for skeletal lesions compared to R‐SS. Clinical and radiology expertise is required to avoid upstaging and overtreatment.